2021
DOI: 10.3390/f12050610
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Moisture Content and Grain Direction on the Elastic Properties of Beech Wood Based on Experiment and Finite Element Method

Abstract: Beech wood (Fagus sylvatica L.) is used in a wide range of wood products. However, the influence of the wood’s moisture content on its mechanical functions will affect its structural strength. It would be complicated and time-consuming to experimentally measure wood’s mechanical functions under different moisture contents. Therefore, it is necessary to establish a prediction formula between the moisture content and elastic constants, and then verify whether its mechanical functions within a wide range of moist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…The authors employed an advanced moisture transport model and multi-surface failure criterion to simulate the moisture-related and brittle failure mechanisms, respectively. Fu et al [66] established the feasibility of evaluating the compressive performance of beech wood at various moisture levels ranging from 5% to 60% using FEM. The use of FEM enabled the authors to overcome complications that would otherwise be associated with the experimental determination of mechanical functions of the beech wood at different moisture loadings.…”
Section: Fea Of Wood Moisture Effect On Mechanical Properties Of Wood...mentioning
confidence: 99%
“…The authors employed an advanced moisture transport model and multi-surface failure criterion to simulate the moisture-related and brittle failure mechanisms, respectively. Fu et al [66] established the feasibility of evaluating the compressive performance of beech wood at various moisture levels ranging from 5% to 60% using FEM. The use of FEM enabled the authors to overcome complications that would otherwise be associated with the experimental determination of mechanical functions of the beech wood at different moisture loadings.…”
Section: Fea Of Wood Moisture Effect On Mechanical Properties Of Wood...mentioning
confidence: 99%
“…Wood moisture content and density also are the basic wood physical parameters which directly relate to the wood mechanical properties (Yin and Liu 2021). However, wood moisture content and density varies from one wood species to another one, even though in the same condition (Fu et al 2021b;Yin and Liu 2021). Thus, finding another indicator to reflect the mechanical properties of wood is important.…”
Section: Vibrational Characteristicsmentioning
confidence: 99%
“…(Lv et al 2018;Xu et al 2020;Fu et al 2021a;Yang and Liu 2021). The scale of tested wood samples can range from non-defective small samples to full-sized wood panels (Ilic 2003;Jiang et al 2008;Katalin et al 2014;Turkot et al 2020;Tu et al 2020;Fu et al 2021b;Zhang et al 2021). Studies researching the relationship between the dynamic modulus of elastic (MOEd) and the static modulus of elastic (MOEs) have primarily used the transverse vibration method, the vertical vibration method, the ultrasonic wave method, the stress wave method, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in the longitude direction, the yield mechanism of wood is mostly dependent on the yield and fold of the wood fiber itself, whereas in the transverse direction, the principal reason is slippage damage between wood fibers. Previous research has also revealed that the mechanical properties of a transverse surface vary depending on whether it is examined in the radial or tangential directions (Fu et al, 2021;Li et al, 2018;Y. Aydın and Ozveren, 2019;Yang and Zhang, 2018).…”
Section: Introductionmentioning
confidence: 99%